Seed priming with ascorbic acid and spermidine regulated auxin biosynthesis to promote root growth of rice under drought stress - Zhang, Kangkang; Khan, Mohammad Nauman; Khan, Zaid; Luo, Tao; Zhang, Biaojin; Bi, Junguo; Hu, Liyong; Luo, Lijun (Frontiers in Plant Science, 2024)
Drought stress severely hampers seedling growth and root architecture, resulting in yield penalties. Seed priming is a promising approach to tolerate drought stress for stand establishment and root development. Here, various seed priming treatments, viz., hydro priming, ascorbic acid priming (AsA), and spermidine priming (Spd), were adopted concerning root morphological, physiological, microstructural, and molecular studies under drought stress on rice variety Hanyou 73. Results demonstrated that drought severely suppressed seedling establishment, while AsA or Spd priming effectively alleviated the inhibitory effects of drought stress, and significantly increased shoot length (24.5-27.9%), root length (34.6-38.8%), shoot dry weight (56.1-97.1%), root dry weight (39.6-40.6%), total root length (47.0-57.8%), surface area (77.0-84.9%), root volume (106.5-109.8%), average diameter (16.4-19.7%), and root tips (46.8-61.1%); meanwhile, priming with AsA or Spd alleviated microscopic and ultrastructural damage from root cell, and improved root activity (183.8-192.0%).The mitigating effects of AsA or Spd priming on drought stress were primarily responsible for decreasing the accumulation of reactive oxygen species by increasing antioxidant activities and osmoprotectant contents, which reduced oxidative stress and osmotic cell potential and facilitated improved water and nutrient absorption in roots.Additionally, seed priming with AsA or Spd substantially improved auxin synthesis by upregulating of OsYUC7, OsYUC11 and, OsCOW1 expression. However, there were certain differences in the defense responses of plants and mechanisms of reducing the damage of drought stress after seed treatment with AsA or Spd. Under stress conditions, AsA had a greater impact on improving the fresh and dry weight of aboveground parts, while Spd affected the concentration of total sugar and total protein in plants. Likewise, the degree of oxidative damage was lowered, and POD and CAT activities were elevated due to Spd priming under water-deficient conditions.